Respuesta :

The solution is [tex]x=14[/tex]

Explanation:

The given expression is [tex]\frac{6}{x^{2} -3x}=\frac{1}{x}- \frac{5}{x^{2} -3x}[/tex]

We need to determine the solution of the expression.

Let us simplify the equation by taking LCM on both sides.

The LCM of [tex]x^{2} -3x[/tex] is [tex]x(x-3)[/tex]

Thus, we have,

[tex]\frac{6}{x^{2} -3x}x(x-3)=\frac{1}{x}x(x-3)- \frac{5}{x^{2} -3x}x(x-3)[/tex]

Simplifying the terms, we get,

[tex]6=x-3-5[/tex]

Subtracting the terms, we have,

[tex]6=x-8[/tex]

Subtracting both sides of the expression by 6, we get,

[tex]0=x-14[/tex]

Adding both sides of the expression by 14, we have,

[tex]14=x[/tex]

Thus, the solution of the equation is [tex]x=14[/tex]

ACCESS MORE